Emerging Antimicrobial Resistance in Helicobacter pylori Strains Isolated from Gastric Disease Patients in Karachi, Pakistan: Antimicrobial Resistance in Helicobacter pylori - Rasheed, Faisal; Khan, Adnan; Farooqui, Amber; Ahmad, Tanvir; Kazmi, Shahana Urooj; Manzoor, Hamid; Akhtar, Syed Shakeel; Quraishy, Mohammed Saeed (Biological Sciences - PJSIR, 2011)